STUDI PENGENDALIAN PEMANAS PADA REAKTOR HIDROGENASI MINYAK NABATI MENJADI GREENDIESEL DENGAN JAKET PEMANAS - Martomo Setyawan (CHEMICA: Jurnal Teknik Kimia, 2014)
Green diesel is the second generation of biodiesel fuel. The advantages of green diesel compared with the first generation of biodiesel are higher cetane number, no waste on the production, and low CO2 emission. Green diesel was made from vegetable oil with a hydrogenation process at the high temperature and high pressure, this process has high risk to explode. This research was to study about heat transfer mechanism from electric heat source to the reactor with avoid explode, by to avoid hydrogen contact with high temperature above 500 OC.The heat transfer mechanism on the hydrogenation reactor was designed from electric heat source transferred to the oil heater and then to the reactor. This research was studied the effluence of the electric voltage to the temperature of the heating oil and the water inside the reactor.The Result of this research showed increasing voltage cause increasing speed of heating. At the all voltage increasing heating speed occur until 40 minutes as linier and after 40 minutes the heating speed decrease as logarithmic. By indirect heating by electric source contact between hydrogen and high temperature surface can be avoided.